Applying Conflict Management Styles to Resolve Task Conflict and Enhance Team Innovation - Anh Tho To; Thi Siem Tran; Kieu Oanh Nguyen; Van Trung Hoang; Kim Phong Thai (Ital Publication, 2021)
Task conflicts among group members have a significant impact on team creativity, so it is critical to identify which conflict resolution styles should be used. This paper aims to examine how various conflict management styles influence team creativity via task conflict. The empirical research was conducted using the Structural Equation Model (SEM) for a sample of 257 employees working for Vietnamese organizations. The results show that dominating style increases task conflict while combining and obliging styles reduce it. To take advantage of the creativity-related benefits associated with task conflict, team leaders should develop an open atmosphere that encourages participants' integrating styles, rather than dominating styles. The negative influence of obliging style reflects Vietnamese culture's high collectivism. The study provides various approaches for task conflict management and also highlights the role of controlling task conflicts in enhancing team innovation. It implies that employees will be able to work better as a team in practice if conflict management strategies are used in a flexible manner. It helps them to build a good connection and successfully implement new ideas. Further research should extend the conclusion of this analysis in various contexts to generalize the findings. Doi: 10.28991/esj-2021-01303 Full Text: PDF